Renovation Trend in Instructional Methods at Electrical Disciplines in Vinh University of Technical Education. - Dang , Quang Khoa (Journal of Technical Education Science, 2008)
In the process of teaching electrical engineering in Vinh University of Technical Teacher Training, the tasks of education and teaching methods which are required to research significantly in the sides of such as fact-analysis, conclusions and suggestions. However, in this article, the author shows only the researching which explains the problems in order to solve those issues, suggests some reality solutions which can be applied to fulfill the renew-method orientations of teaching electrical engineering in the Vinh University of Technical Teacher Training